Prevalence and trends in Australian adolescents' adherence to 24-hour movement guidelines: findings from a repeated national cross-sectional survey - Maree Scully; Claudia Gascoyne; Melanie Wakefield; Belinda Morley (BMC, 2022)
Abstract Background 24-hour movement guidelines recommend a healthy balance of high levels of physical activity, low levels of sedentary behaviour and appropriate sleep duration each day. At present, surveillance data on how Australian adolescents are performing against these guidelines are lacking. This study aims to describe the extent to which Australian secondary school students are adhering to the physical activity, sedentary recreational screen time and sleep duration recommendations outlined in the national 24-hour movement guidelines for children and young people. It also examines whether there are socio-demographic differences in levels of compliance and if there have been significant changes in these behaviours over time. Methods A repeated national cross-sectional survey of students in grades 8 to 11 (ages 12-17 years) was conducted in 2009-2010 (n=13,790), 2012-2013 (n=10,309) and 2018 (n=9,102). Students' self-reported physical activity, screen time and sleep behaviours were assessed using validated instruments administered in schools via a web-based questionnaire. Results In 2018, around one in four students (26%) did not meet any of the 24-hour movement guidelines, while only 2% of students met all three. Adherence to the sleep duration recommendation was highest (67%), with substantially smaller proportions of students meeting the physical activity (16%) and screen time (10%) recommendations. Differences in adherence by sex, grade level and socio-economic area were apparent. Students' compliance with the screen time recommendation has declined over time, from 19% in 2009-2010 to 10% in 2018. However, there has been no significant change in the proportion meeting the physical activity (15% in 2009-2010 cf. 16% in 2018) and sleep duration (69% in 2009-2010 cf. 67% in 2018) recommendations. Compliance with all three guidelines has remained very low (<3%) across each survey round. Conclusions There is considerable scope to improve Australian adolescents' physical activity and sedentary behaviours in line with the national 24-hour movement guidelines. Policy proposals and environmental interventions, particularly those focused on replacing sedentary screen time with physical activity (e.g. promotion of active commuting to/from school), are needed to better support Australian adolescents in meeting the 24-hour movement guidelines.